Identifying the distracting aspects of electronic advertising billboards: A driving simulation study. (September 2020) - Meuleners, Lynn; Roberts, Paul; Fraser, Michelle
Highlights: A simulator study examined the impact of digital billboards on driving performance. The presence of digital billboards negatively affected driving performance. Mean speed, speed variability, lane position, and vehicle headway were affected. Simple billboard content and longer dwell times were safer. Abstract: The aim of the study was to investigate the impact of digital billboards on driving performance and visual attention. The impact of dwell time, location and content of digital billboards on driving behaviour was also examined. A 3 × 2 × 2 × 2 experimental study was undertaken using a laboratory driving simulator and data analysed using factorial four-way analysis of variance. A total of 96 participants completed the study, ranging in age from 18 to 76 years. On sections of roads containing billboards, participants drove at lower mean speeds (p < 0.001), had more speed variability (p < 0.001), more variability in lane position (p < 0.001), more time spent at high risk headway < two seconds (p = 0.013), more time spent at high risk headway <0.25 s (p = 0.002) and had more visual fixations (p = 0.01), compared to control sections of road with no billboards. Billboards with simple (versus complex) content presented at a long dwell time (60 s versus 40 or 20 s) had the least negative impact on driving outcomes. Billboards with complex content had similar negative effects on driving, regardless of dwell time. In addition, post-mounted roadside billboards (versus bridge mounted) with 60 s dwell times had the least negative impact on driving. While the presence of digital billboards negatively affected driving performance, simple billboard content and longer dwell times were safer. The results of the study will assist in the development of evidence-based guidelines for digital billboards.